Electrospun carbon nanofiberic coated with ambutan-like NiCo2O4 microspheres as electrode materials. (1st March 2017) - Chen, Hua; Jiang, Guohua; Yu, Weijiang; Liu, Depeng; Liu, Yongkun; Li, Lei; Huang, Qin
Abstract: Abstract : The novel Three-dimensional rambutan-like NiCo2 O4 microspheres have been successfully coated onto surface of carbon nanofibers (CNFs) to form NiCo2 O4 –CNFs hybrids. The composition and microstructure of NiCo2 O4 –CNFs were characterized by the field-emission scanning electronmicroscopy, x-ray photoelectron spectroscopy, transmission electron microscopy, and x-ray diffractometer. The obtained NiCo2 O4 –CNFs exhibited a specific capacity of 160 mAh/g at 1 mA/cm 2 in 2 M potassium hydroxide aqueous solution. The specific capacity gradually increases with the increasing of cycles; and after 3000 cycles, the specific capacity still can be remained over 90%.